Study protocol for a mixed methods convergent investigation of family domestic and sexual violence in multiple sclerosis and broader neurology in Australia - Cassie Nesbitt; Genevieve Rayner; Kristen Timmens; Christina Kazzi; Rubina Alpitsis; Emma Foster; Jason Ray; Joanne Crosby; Helmut Butzkueven; Anneke Van Der Walt; Vilija G. Jokubaitis (PLoS ONE, 2026)
Background People with disabilities experience disproportionately high rates of family, domestic, and sexual violence (FDSV), yet recognition and response in neurological healthcare, including multiple sclerosis (MS), remain underexplored. The study is informed by evidence-based frameworks for healthcare responses to family, domestic, and sexual violence, including the World Health Organization’s Listen, Inquire, Validate, Enhance safety, Support access (LIVES) approach and Victoria, Australia’s Multi-Agency Risk Assessment and Management (MARAM) framework. These models share core principles of trauma-informed practice, structured risk assessment, and coordinated response, providing a foundation for investigating how such approaches can be applied and adapted within neurological care. Objectives This study aims to estimate the prevalence and describe the forms of FDSV experienced by people with MS, identify associated social, clinical, and contextual factors, and document current neurology practices for recognising and responding to FDSV. Comparative qualitative analysis across MS, epilepsy, and headache will assess whether findings are condition-specific or shared across neurology to inform future strategies. Methods and analysis A convergent mixed-methods design will be applied across six study arms. Quantitative components include screening approximately 1,000 people with MS, registry linkage, and surveys with at least 100 participants assessing trauma exposure, wellbeing, and disability-related violence. Qualitative interviews with people with MS, epilepsy, and headache, and clinicians (n ≈ 64 total) will explore experiences, clinical practice, and barriers and enablers to implementing evidence-based frameworks. Data will be integrated through triangulation to identify convergent and divergent patterns. Discussion Findings will provide foundational evidence on how MS and other neurological conditions intersect with experiences of FDSV, guiding trauma-informed training, policy, and practice across neurology. Registration Australian New Zealand Clinical Trials Registry (ANZCTR), ACTRN390279.